1986
DOI: 10.1144/gsl.eng.1986.002.01.09
|View full text |Cite
|
Sign up to set email alerts
|

Landslides caused by rapid groundwater changes

Abstract: A severe rainfall event occurs once every two years in Hong Kong, causing widespread landslides which result in human casualties and much damage. It has recently been established that these landslides are caused largely by short-period, high-intensity rainfall, with nearly all failures occurring within a few hours of peak intensity. The failures are therefore attributable mainly to rapid transient variations in groundwater conditions. These findings are in contradiction to previously accepted theories on failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The changeable nature of such pipe systems, especially seasonally, with silting up and collapse causing blockage can cause backing up of the infiltrated water and local increase in water pressure as identified in the physical models of Pierson (1983). At depth preferential, channels/pipes can cause a rapid infiltration and response of groundwater pressure to rainfall (Premchitt et al, 1986), much quicker than would be predicted from an isotropic infiltration approach (Lumb, 1962;Ng and Shi, 1998;Iverson, 2000). A proposed framework for the timing of landslides is presented in Table I and discussed in more detail in Hencher et al (2006).…”
Section: Timing Of Landslidesmentioning
confidence: 99%
“…The changeable nature of such pipe systems, especially seasonally, with silting up and collapse causing blockage can cause backing up of the infiltrated water and local increase in water pressure as identified in the physical models of Pierson (1983). At depth preferential, channels/pipes can cause a rapid infiltration and response of groundwater pressure to rainfall (Premchitt et al, 1986), much quicker than would be predicted from an isotropic infiltration approach (Lumb, 1962;Ng and Shi, 1998;Iverson, 2000). A proposed framework for the timing of landslides is presented in Table I and discussed in more detail in Hencher et al (2006).…”
Section: Timing Of Landslidesmentioning
confidence: 99%
“…This shows that during the process of changing landslide proportion in the watershed over the years, the ecohydrological processes were altered. The variation in ecohydrological processes in landslide areas could be because the failures caused by landslide are mainly attributed to rapid transient variations in groundwater conditions [57].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that for certain landslides high peak intensity can contribute significantly to triggering a landslide independent of the overall storm depth, duration or intensity (Corominas et al, 2002;Yu et al, 2006). This idea is supported for example by observations that landslides are commonly initialized within hours of the peak intensity (Premchitt et al, 1986). The precipitation rank and z-score among the four products for each landslide event were also computed for the day of the landslide as well as for the full May 2015-May 2020 precipitation record.…”
Section: Precipitation Inter-comparison and Computation Of Storm Charmentioning
confidence: 92%